Apakah Literasi Mempengaruhi Penerimaan Zakat? - Clarashinta Canggih; Rachma Indrarini (JESI (Jurnal Ekonomi Syariah Indonesia), 2021)
Zakat is not only relates to ilahiyah worship but also relates to muamalah which has social and economic value. Zakat can be used as a tool to increase welfare and eradicate poverty. Since, Indonesia has large Muslim population, it supposes to has large amount of Zakat. However, the actual recorded zakat collection is still very far from the potency. People zakat literacy about zakat obligations is also low. This paper aims to see the impact pf zakat literacy to zakat collection by OPZ. This research was an associative quantitative study using PLS-SEM bootstrap with WarpPLS5. The object of this research was 9 OPZs (8 LAZNAS and 1 BAZ) which have representative offices in Surabaya. Respondents of this study were muzakki who represented OPZ. The results of this study indicated that zakat literacy has a significant effect on the realization of zakat collection, however the intention to pay zakat does not mediate the relationship between literacy and the realization of zakat collection. This research can be used to identify steps to increase zakat collection.